An examination of artefacts in market-oriented firms. Issue 1 (11th November 2020) - O'Regan, Cynthia; Dwyer, Tomás; Mulligan, Julie
Abstract : Purpose: The purpose of this paper is to examine the nature and influence of artefacts in market-oriented firms. Design/methodology/approach: Document analysis, direct observation and 14 key informant interviews were undertaken in 6 case study of companies. Findings: The research investigated the nature and influence of four categories of artefacts in market-oriented firms, specifically, stories, arrangements, rituals and language. The four categories of artefacts were found to embody, reinforce, create and compliment the values, norms and behaviours of a market-oriented culture. Market-oriented artefacts are thus core to a market-oriented culture and in developing a market orientation. Research limitations/implications: The four categories of artefact, namely, stories, arrangements, rituals and language embody a market-oriented culture; these artefacts are necessary to implement market-oriented behaviours. Artefacts play a significant cultural and behavioural part in creating a market-oriented culture. Practical implications: To be a market-oriented firm means implementing a market-oriented culture. This paper requires managers to assess the degree to which they have developed and used market-oriented artefacts in the establishment and strengthening of a market-oriented culture. Originality/value: This paper addresses the limited understanding of market-oriented artefacts as an element of a market-oriented culture.